Antropologia medica nella crisi ambientale. Determinanti biosociali, politica e campi di causazione - Elisa Pasquarelli; Andrea Filippo Ravenda (Archivio Antropologico Mediterraneo)
The papers result from a public debate on the intertwining of health, environment and risk as emerged from a panel focused on these topics of the 2nd national conference of the Italian Society of Medical Anthropology (Perugia June 14-16, 2018) dedicated to the memory of its founder Tullio Seppilli. The authors discuss – within different interpretative perspectives and in reference to plural contexts – the relationship between environment and health protection and the ways in which the presence of environmental and/or industrial risk factors stimulate sometimes conflicting responses in social actors with diversified interests. In such a complex framework, this special issue hosts theoretical contributions and ethnographic researches that, in their multiplicity, explore the global articulations of the environmental crisis with its local peculiarities embodied in the experiences of the people who live, work and fall ill in territories damaged or contaminated.